Development of a Panel of Genotyping-in-Thousands by Sequencing in Capsicum - Jo, Jinkwan; Kim, Youngin; Kim, Geon Woo; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2021)
Genotyping by sequencing (GBS) enables genotyping of multiple loci at low cost. However, the single nucleotide polymorphisms (SNPs) revealed by GBS tend to be randomly distributed between individuals, limiting their direct comparisons without applying the various filter options to obtain a comparable dataset of SNPs. Here, we developed a panel of a multiplex targeted sequencing method, genotyping-in-thousands by sequencing (GT-seq), to genotype SNPs in Capsicum spp. Previously developed Fluidigm® SNP markers were converted to GT-seq markers and combined with new GT-seq markers developed using SNP information obtained through GBS. We then optimized multiplex PCR conditions: we obtained the highest genotyping rate when the first PCR consisted of 25 cycles. In addition, we determined that 101 primer pairs performed best when amplifying target sequences of 79 bp. We minimized interference of multiplex PCR by primer dimer formation using the PrimerPooler program. Using our GT-seq pipeline on Illumina Miseq and Nextseq platforms, we genotyped up to 1,500 (Miseq) and 1,300 (Nextseq) samples for the optimum panel size of 100 loci. To allow the genotyping of Capsicum species, we designed 332 informative GT-seq markers from Fluidigm SNP markers and GBS-derived SNPs. This study illustrates the first application of GT-seq in crop plants. The GT-seq marker set developed here will be a useful tool for molecular breeding of peppers in the future.